2021
DOI: 10.1101/2021.02.18.21251932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial use in COVID-19 patients in the first phase of the SARS-CoV-2 pandemic: Rapid review and evidence synthesis

Abstract: Background: As the numbers of people with COVID-19 continue to increase globally, concerns have been raised regarding the widespread use of antibiotics for the treatment of COVID-19 patients and its consequences for antimicrobial resistance during the pandemic and beyond. The scale and determinants of antibiotic use in the early phase of the pandemic, and whether antibiotic prescribing is beneficial to treatment effectiveness in COVID-19 patients, are still unknown. Unwarranted treatment of this viral infecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…A meta-analysis shows that approximately 75% of patients with COVID-19 admitted to hospitals were given an antibiotic; yet, only 8% of the patients were confirmed with bacterial co-infection [ 4 ]. A similar pattern is seen among critically ill patients in which the rate of superinfection in COVID-19 patients was 13.5%, but 75.4 to 94% of them were treated with antibiotics [ 3 , 5 ].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…A meta-analysis shows that approximately 75% of patients with COVID-19 admitted to hospitals were given an antibiotic; yet, only 8% of the patients were confirmed with bacterial co-infection [ 4 ]. A similar pattern is seen among critically ill patients in which the rate of superinfection in COVID-19 patients was 13.5%, but 75.4 to 94% of them were treated with antibiotics [ 3 , 5 ].…”
Section: Introductionsupporting
confidence: 60%
“…Despite a relatively low bacterial co-infection rate, the prevalence of antibiotic usage in patients with COVID-19 infection was nevertheless considerably high. A research rapidly reviews studies researching on antibiotic usage in the early phase of pandemic revealed that 82.3% of 10, 329 COVID-19 patients (82.3%) received antibiotics therapy without regard to the severity of COVID-19 infection [ 3 ]. A meta-analysis shows that approximately 75% of patients with COVID-19 admitted to hospitals were given an antibiotic; yet, only 8% of the patients were confirmed with bacterial co-infection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies confirm that most hospitalized patients with COVID-19 are managed with broad-spectrum antimicrobials with unproven efficacy [ 47 ]. Cong et al (2021) highlighted that the percentage of antibiotic prescriptions for patients with both severe/critical disease nearly equaled the percentage for patients with mild/moderate disease, even though more critically ill patients are at greater risk of developing secondary bacterial infections [ 3 ]. These unnecessary antimicrobials and excessive prescribing for mild and moderate COVID-19 will probably increase risks for adverse events and selective development of multidrug-resistant bacterial pathogens at local healthcare and regional levels.…”
Section: Discussionmentioning
confidence: 99%
“…The ambiguity of this serious disease over the first wave swept worldwide, posing considerable challenges, including diagnosis, management, provision of resources, and ethical consideration to all global healthcare institutions. Therefore, the catastrophic situation resulted in many patients with a wide range of clinical manifestations ranging from asymptomatic to fatal diseases that required critical care, including ICU admission [ 3 ]. Furthermore, in critical care settings, research indicates that COVID-19 is associated with increased mortality of up to 50% with pre-existing comorbidities, such as diabetes, hypertension, and renal and cardiovascular complications, in critical care settings [ 4 ].…”
Section: Introductionmentioning
confidence: 99%